Influência do histórico familiar de hipertensão arterial, estresse mental e do exercício físico aeróbio na modulação autonômica cardíaca e na pressão arterial laboratorial e ambulatorial em adultos jovens - Queiroz, Marilene Gonçalves (2023)
Children of hypertensive parents (FH+) have hemodynamic dysfunctions, both at rest and in stressful situations. Aerobic physical exercise is recommended for the prevention and non-pharmacological treatment of these disorders. Despite the clinical success, studies that evaluate outpatient autonomic modulation are controversial and scarce, especially regarding exercise. Therefore, the objective of this study was to evaluate whether the family history of arterial hypertension influences cardiac autonomic modulation and laboratory BP during breathing, under mental stress and after aerobic exercise. Likewise, investigate whether the family history of arterial hypertension is capable of influencing HRV and ambulatory BP at rest and 24 hours after aerobic exercise. Therefore, 22 FH+ (24.65 ± 4.05 years; 110.48 ± 11.24/ 69.68 ± 6.00 mmHg) and 22 FH- (23.70 ± 5.25 years; 112.57 ± 11.40/68.73 ± 6.86 mmHg) were randomly manifested in the exercise session (SE) and the control session (SC). BP, HR and HRV were evaluated at rest. Then, the volunteers were allowed a session of aerobic physical exercise. Soon after, I got 5 minutes of immediate recovery and 1 hour of laboratory recovery. Subsequently, the Stroop test and 5 minutes of post metal stress recovery were performed. Finally, ABPM and Holter for 24 hours were placed. In the control session, the volunteers remained seated for 30 min, instead of performing the exercise. At first, we evaluated laboratory BP and HRV. There was no difference between the FH+ and FH- groups for hemodynamic variables at rest, during and post-exercise. In the second moment, we evaluated the influence of mental stress and family history of hypertension on hemodynamic modulation at rest and after an aerobic exercise session. There was no difference between the FH+ and FH- in BP both in the control session and in the exercise session. However, the Ln-HF (u.n) at rest was higher in the FH- group in the exercise session (FH+: 3.42 ± 0.54; FH-: 4.22 ± 0.30; p < 0.01) and LF ( ms) of lower rest in the FH- group regardless of the session (FH+: 6.77 ± 0.94; FH-: 6.05 ± 1.35; p = 0.02). Aerobic exercise was able to attenuate the SBP/DBP reactivity to mental stress, however, it sharply increased the HR response in both groups (p < 0.01). In the third moment, we evaluated the influence of family history of hypertension and aerobic exercise on ambulatory BP and HRV. There was a difference in ambulatory HRV between FH+ and FH- (p ≤ 0.05). DBP (mmHg) during sleep was higher in FH+ (SC: 61.45 ± 5.72; SE: 58.21 ± 7.60) than FH- (SC: 60.33 ±7.55 SE: 59 .35 ±7.69), but we found no difference between groups in SBP. Moderate-intensity aerobic exercise promoted DBP hypotension during sleep in FH+ (p < 0.01) and did not change ambulatory HR (p = 0.95). The HRV indices of the fever domain had a greater predominance of sympathetic cardiac autonomic modulation in FH+ when compared to FH- regardless of the patient session (p ≤ 0.05). It is concluded that young FH+ have preserved laboratory hemodynamic modulation. So, as during mental stress. However, moderate-intensity aerobic exercise was able to reduce BP reactivity, however, it increased sympathetic cardiac autonomic modulation to mental stress in young adults, regardless of family history of arterial hypertension. FH+ youngsters have greater ambulatory DBP and dysfunctions in ambulatory cardiac autonomic modulation at rest, and preserved after exercise.